Kinerja Pertumbuhan dan Kelangsungan Hidup Benih Ikan Depik (Rasbora tawarensis) yang diberi Daphnia sp. dengan Pemberian Pakan yang Berbeda - Cut Nur Delima; Cut Mulyani; Muhammad Fauzan Isma (Jurnal Ilmiah Samudra Akuatika, 2021)
: Depik fish (Rasbora tawarensis) is a type of freshwater fish that lives in Laut Tawar Lake, Central Aceh Regency. Depic fish is a pelagic endemic fish. This study aims to determine the best feed for (Daphnia sp.) on the growth and survival of depic fish (Rasbora tawarensis) seed. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications, namely P1 (Daphnia sp. Given powder pellets). P2 (Daphnia sp. Given yeast feed). P3 (Daphnia sp. Given Spirulina) and P4 (Daphnia sp. Given Green water). Each treatment uses seeds measuring 2-3 cm. The parameters observed during the study were water quality, survival rate (SR), absolute weight growth (PBM), absolute length growth (PPM), and specific growth rate (SGR.The results of observations based on analysis of variance showed that Daphnia sp. Has significant effect (P <0.05) on absolute weight growth, absolute length growth but has no significant effect on specific growth rates and survival. The best treatment for different feeding in this study was P2 (yeast feeding) and P3 (spirulina feeding) treatment.